The effectiveness of promotion activities by Pusat Zakat Melaka toward zakat collection among Malay entrepreneur in Melaka Tengah / Nurhazisafrina Mohammad (Faculty of Business and Management, 2006)
This study focuses on "The Effectiveness of Promotion Activities by Pusat Zakat Melaka toward Zakat Collection among Malay Entrepreneur in 'Melaka Tengah'. The objective is to determine the promotion tools that have given the greatest exposure on zakat on business to the Malay entrepreneurs, to identify the promotional effect attained through PZM promotional efforts and to establish the relationship between the promotional effect and zakat collection by Pusat Zakat Melaka. The sampling technique that has been used was the probability sampling where 50 respondents were chosen to answer the questionnaires. The result of the findings shows that the promotion activities through advertisement at mass media and electronics as well as zakat campaign were given the greatest exposure on zakat on business, while the promotional effect has no relationship with zakat collection.